Proceedings of the 33rd Annual ACM/IEEE Symposium on Logic in Computer Science 2018
DOI: 10.1145/3209108.3209183
|View full text |Cite
|
Sign up to set email alerts
|

Free Higher Groups in Homotopy Type Theory

Abstract: Given a type A in homotopy type theory (HoTT), we can define the free ∞-group on A as the loop space of the suspension of A + 1. Equiv-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 17 publications
(13 reference statements)
0
23
0
Order By: Relevance
“…Of course, the intermediate goal that this paper is working towards is the statement that 2LTT can eat HoTT. Even a much weaker question, namely whether the initial ∞-CwF has trivial fundamental group, would be very interesting; but already this seemingly much simpler problem appears to be highly non-trivial, and similar results for seemingly simpler situations [65]- [67] suggest that a solution will require new techniques.…”
Section: Open Problems and Future Directionsmentioning
confidence: 99%
“…Of course, the intermediate goal that this paper is working towards is the statement that 2LTT can eat HoTT. Even a much weaker question, namely whether the initial ∞-CwF has trivial fundamental group, would be very interesting; but already this seemingly much simpler problem appears to be highly non-trivial, and similar results for seemingly simpler situations [65]- [67] suggest that a solution will require new techniques.…”
Section: Open Problems and Future Directionsmentioning
confidence: 99%
“…This means that a normalisation function is only definable for sets a : A with a decidable equality. The general problem of whether F(A) is a set, if A is, is still open -in [KA18] it is shown to be the case, if we 1-truncate the HIT.…”
Section: Introductionmentioning
confidence: 99%
“…This construction is completely reasonable without the assumption that A is a set, and it therefore defines the free higher group (cf. [21]); from now on, we write F A for it: F A :≡ Ω(hcolim(A ⇒ 1)).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known in the community how to circumvent the problem if A has decidable equality. However, the only piece of progress on the general question that we are aware of is the result in [21], where it is shown that all fundamental groups [28,Chp 6.11] are trivial. In other words: Instead of showing that everything above truncation level 0 is trivial, the result shows that a single level is trivial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation